1993
DOI: 10.1073/pnas.90.5.1942
|View full text |Cite
|
Sign up to set email alerts
|

Cooperativity in protein-folding kinetics.

Abstract: How does a protein find its native state without a globally exhaustive search? We propose the "HZ" (hydrophobic zipper) hypothesis: hydrophobic contacts act as constraints that bring other contacts into spatial proximity, which then further constrain and zip up the next contacts, etc.In contrast to helix-coil cooperativity, HZ-heteropolymer collapse cooperatvity is driven by nonlocal interactions, causes sheet and irregular conformations in addition to helices, leads to secondary structurs concurrentiy with ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
268
1
3

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 446 publications
(293 citation statements)
references
References 83 publications
21
268
1
3
Order By: Relevance
“…Using a cubic lattice simulation, Shakhnovich (Abkevich et al 1995) found that NLIs contribute to a faster rate of folding. However, the results of many other studies support the counterhypothesis that the folding mechanism is dominated by LIs, while the non-local ones provide non-specific stabilization of the compact conformers (Anfinsen and Scheraga 1975;Harrison and Durbin 1985;Wright et al 1988;Rooman et al 1992;Dill et al 1993;Weikl and Dill 2003) and nucleation (Wetlaufer 1973;Daggett and Fersht 2003;Kihara 2005) The question of whether the LIs or NLIs are more important or dominant in the initiation of folding, or for determination of the direction and rate of the folding transition remains open, and is the subject of the present review. Fig.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Using a cubic lattice simulation, Shakhnovich (Abkevich et al 1995) found that NLIs contribute to a faster rate of folding. However, the results of many other studies support the counterhypothesis that the folding mechanism is dominated by LIs, while the non-local ones provide non-specific stabilization of the compact conformers (Anfinsen and Scheraga 1975;Harrison and Durbin 1985;Wright et al 1988;Rooman et al 1992;Dill et al 1993;Weikl and Dill 2003) and nucleation (Wetlaufer 1973;Daggett and Fersht 2003;Kihara 2005) The question of whether the LIs or NLIs are more important or dominant in the initiation of folding, or for determination of the direction and rate of the folding transition remains open, and is the subject of the present review. Fig.…”
Section: Introductionmentioning
confidence: 80%
“…In these models, the NLIs are assumed to have smaller role and can be non-specific. In the zipping and assembly (ZA) mechanism suggested by Dill's group (Dill et al 1993), local structuring happens first at independent sites along the chain, then those structures either grow (zip) or coalescence (assemble) with other structures (Ozkan et al 2007;Dill et al 2008;Shell et al 2009). Dill argues that the ZA mechanism is a model for the physical pathways of protein folding.…”
Section: O'neill Et Al (O'neill and Robert Matthews 2000)mentioning
confidence: 99%
“…The early collapse of the polypeptide chain is represented by the steep drop at the top of figure 4. That this is indicated to occur at relatively low values of Q reflects the fact that few native-like contacts may be needed for collapse to occur; the driving force is likely to be simply the burial of hydrophobic groups [6,36]. From this highly heterogeneous collapsed state, nativelike structure develops independently in the two structural domains, and hence intermediates are formed.…”
Section: Schematic Energy Surface For Lysozyme Foldingmentioning
confidence: 99%
“…Side chain interactions between two nonpolar bution to protein stability. Exclusion of water from hydrophobic surfaces is thought to occur early in the folding pathway (Dill et al, 1993), and there is evidence that hydrophobic clusters arise in denatured states (Neri et al, 1992;Shortle, 1993) and in folding intermediates (Martensson et al, 1993). A recent statistical study of protein crystal structures has revealed strong correlations for specific pairs of amino acids spaced i, i + 4 in a-helices; the strongest preferences are for salt bridges, Leu-Leu and Phe-Met (Klingler & Brutlag, 1995).…”
mentioning
confidence: 99%